Theories and Evidence of Urban Dilemma in Peru: Why did we Grow Economically with Violence? (2000-2012) - Hernández Breña, Wilson (2016)
In the last decade, Peru has experienced what is known as the urban dilemma: the country has grown economically and, in tandem with greater urbanization, urban violence has increased. The objective of this research is to study that dilemma through the identification of determinants of urban violence (thefts per 100,000 inhabitants). In addition to the other two variables of the urban dilemma (GDP per capita and population density), explanatory variables of economic inequalities and poverty are included alongside others linked to theories that explain violence.  Corrected statistics from the Peruvian Police (more reliable than those of the Public Ministry) are used, and a panel data model with regional data (2000-2012) is employed. The results confirm the existence of the urban dilemma. There is important evidence of a reduction in the costs of offending and of the influence of economic as well as social variables that explain violence.